AB0560 Performance characteristics of response scales of activity and function measures of ankylosing spondylitis in turkish: numerical rating scale vs visual analog scale. (23rd January 2014) - Akat, K.; Solmaz, D.; Sari, I.; Onen, F.; Akkoc, N.; Akar, S.
Abstract : Background: Bath ankylosing spondylitis disease activity index (BASDAI) (1 ) and Bath ankylosing spondylitis functional index (BASFI) (2 ) are frequently used self-reported measures of disease activity and function. Previously we showed the validation of Turkish versions of these indices. The original answer modality based on 10-cm VAS scales. However, it has been reported that numerical rating scale (NRS) is relatively simple and easy in application and scoring, even when administered verbally. Objectives: The aim of this study was to compare the performance characteristics of two answer modalities for BASDAI and BASFI in patients with AS and to show validity and reliability of NRS version in Turkish. Methods: BASDAI and BASFI were simultaneously employed with both original answer modality and an 11-point NRS. Testing was performed on baseline and next day under standardized conditions. Baseline and next day data were used to assess test/retest reliability. Internal consistency was assessed by using intraclass correlation coefficients (ICC). Construct validity was determined by association between BASDAI/BASFI and DFI, ASDAS, global disease activity, pain scores, ASQOL, and SF-36. The sensitivity to change of NRS version of BASDAI and BASFI was estimated based on the comparison of baseline and follow-up data of patients whose treatment was changed on baseline visit. Feasibility and face validity of NRS answer modalities were also tested. Results: A total 114 consecutive patients with AS (87 [76%] male, mean age was 39.8 ±10.9 years) according to the modified New York criteria were included in the study. There were perfect agreement between the total scores of each instrument on day 0 and day 1 (ICC values were between 0.959-0.988). NRS answering format provided higher internal consistency estimates (ICC for BASDAI-NRS=0.742, for BASFI-NRS=0.781) than VAS format (ICC for BASDAI-VAS=0.630, for BASFI-VAS=0.742). Scores of the both answering modality of each instrument were correlated with ASDAS, DFI, scores of patient global assessment of disease activity and patient reported pain (VAS), ASQOL, and scores of SF-36. BASDAI and BASFI scores showed significant improvement in NSAID or anti-TNF started patients on baseline. Response time for BASDAI and BASFI was significantly shorter in NRS answer modality. Our patients have found NRS modality easier to complete and more appropriate (p<0.001). Also they reported that NRS was more preferable (p<0.001) than VAS. Conclusions: Our results showed the validity of NRS version of BASDAI and BASFI. It seems that NRS can also be used as an answering format for BASDAI and BASFI in Turkish AS patients. References: Garrett S, Jenkinson T, Kennedy LG, Whitelock H, Gaisford P, Calin A. A new approach to defining disease status in ankylosing spondylitis: the Bath Ankylosing Spondylitis Disease Activity Index. J Rheumatol. 1994;21(12):2286-91. Calin A, Garrett S, Whitelock H, Kennedy LG, O'Hea J, Mallorie P, et al. A new approach to defining functional ability in ankylosing spondylitis: the development of the Bath Ankylosing Spondylitis Functional Index. J Rheumatol. 1994;21(12):2281-5. Disclosure of Interest: None Declared